Managing chronic pain in elderly patients requires a CHANGE of approach. (June 2014) - Kress, Hans-Georg; Ahlbeck, Karsten; Aldington, Dominic; Alon, Eli; Coaccioli, Stefano; Coluzzi, Flaminia; Huygen, Frank; Jaksch, Wolfgang; Kalso, Eija; Kocot-Kępska, Magdalena; Mangas, Ana Cristina; Margarit Ferri, Cesar; et al.
Abstract In many countries, the number of elderly people has increased rapidly in recent years and this is expected to continue; it has been predicted that almost a quarter of the population in the European Union will be over 65 years of age in 2035. Many elderly people suffer from chronic pain but it is regularly under-treated, partly because managing these patients is often complex. This paper outlines the extent of untreated pain in this population and the consequent reduction in quality of life, before articulating the reasons why it is poorly or inaccurately diagnosed. These include the patient's unwillingness to complain, atypical pain presentations, multiple morbidities and cognitive decline. Successful pain management depends upon accurate diagnosis, which is based upon a complete history and thorough physical examination, as well as an assessment of psychosocial functioning. Poor physician/patient communication can be improved by using standardized instruments to establish individual treatment targets and measure progress towards them. User-friendly observational instruments may be valuable for patients with dementia. In line with the widely accepted biopsychosocial model of pain, a multidisciplinary approach to pain management is recommended, with pharmacotherapy, psychological support, physical rehabilitation and interventional procedures available if required. Declining organ function and other physiological changes require lower initial doses of analgesics and less frequent dosing intervals, and the physician must be aware of all medications that the patient is taking, in order to avoid drug/drug interactions. Non-adherence to treatment is common, and various strategies can be employed to improve it; involving the elderly patient's caregivers and family, using medication systems such as pill-boxes, or even sending text messages. In the long term, the teaching of pain medicine needs to be improved – particularly in the use of opioids – both at undergraduate level and after qualification.